2016
DOI: 10.3389/fsoc.2016.00007
|View full text |Cite
|
Sign up to set email alerts
|

The Limits of Heteronormative Sexual Scripting: College Student Development of Individual Sexual Scripts and Descriptions of Lesbian Sexual Behavior

Abstract: Simon and Gagnon's sexual script theory identifies multitiered influences, which shape individual ideas about sexual relationships. The cultural celebration of heterosexuality as the accepted standard dominates major social institutions and permeates cultural sexual messages. The reception of these heteronormative messages influences the formation of individualized sexual scripts; however, how individuals apply these individualized scripts to understanding the sexual lives of others is little understood. More … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 35 publications
(30 reference statements)
0
7
0
1
Order By: Relevance
“…Previous literature has illustrated gaps in defining same-sex /gender sex, especially for WSW Carpenter, 2002;Dion & Boislard, 2020;Pham, 2016). Whilst for some people, anal sex may be a key identifier for sex between men and oral sex may be a key identifier for sex between women (Dion & Boislard, 2020;Pham, 2016), definitions of first sex and virginity can be difficult and variable among LGB+ individuals, and are often tied to heteronormative frameworks that are under-discussed among the LGB+ community (Averett et al, 2014;Dion & Boislard, 2020;Pham, 2016). This was also reported by participants in the present study, which led to confusion, particularly among female participants who reported that this delegitimized their first sexual experience.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous literature has illustrated gaps in defining same-sex /gender sex, especially for WSW Carpenter, 2002;Dion & Boislard, 2020;Pham, 2016). Whilst for some people, anal sex may be a key identifier for sex between men and oral sex may be a key identifier for sex between women (Dion & Boislard, 2020;Pham, 2016), definitions of first sex and virginity can be difficult and variable among LGB+ individuals, and are often tied to heteronormative frameworks that are under-discussed among the LGB+ community (Averett et al, 2014;Dion & Boislard, 2020;Pham, 2016). This was also reported by participants in the present study, which led to confusion, particularly among female participants who reported that this delegitimized their first sexual experience.…”
Section: Discussionmentioning
confidence: 99%
“…Sexual Script Theory describes how an individual develops sexual scripts based on socio-cultural norms and individual experience (Simon & Gagnon, 1986;Pham, 2016). A sexual script is an internalized behavioral framework that guides an individual within their sexual experiences.…”
Section: Sexual Scriptsmentioning
confidence: 99%
See 1 more Smart Citation
“…Por otro lado, aplicando a este ámbito las teorizaciones de Wittig sobre la heterosexualidad y su radical desencialización de las categorías sexogenéricas (Wittig, 1992a(Wittig, , 1992b, también se podría concluir que la disidencia sexual conforma un espacio totalmente ajeno al orden heteronormativo que se rige en base a sus propias reglas, en un espacio de mayor libertad respecto al orden sexual heteropatriarcal. A su vez, aquellas personas que subvierten la heteronormatividad, al no estar tan representadas en los medios, tampoco disponen de tantas referencias ni de tantos modelos establecidos (Pham, 2016;Enguix y González, 2018), y sus propios medios cuentan con otro tipo de representaciones que, aun siendo minoritarias, fomentan valores más igualitarios que muestran mayor diversidad (Milillo, 2008). En este sentido, podríamos afirmar que, al no corporizar la identidad normativa que las industrias culturales están destinadas a producir, las personas LGTBIQ+ participantes quedan, en cierta manera, más al margen del influjo de ese biopoder mediático patriarcal y heteronormativo.…”
Section: Conclusionesunclassified
“…Overall, the scripts for consent are highly gendered and overtly heteronormative. Young people rely heavily on the heteronormative scripts they have learned, and apply this model to understand sex in same sex relationships (Pham, 2016). Additionally, it has been suggested that young people need to abide by heternormative scripts in order to participate in the dating culture they exist within (Toprak, 2020).…”
Section: Introductionmentioning
confidence: 99%